Organizational Climate and Productivity: The Case of a Credit Union in Ecuador - Mendoza, Yadira Tatiana López; Colamarco, Ignacio Wilhem Loor; Meléndez, Hilarión José Vegas; Martínez, María Elena Moya (Journal of Posthumanism, 2025)
This study analyzes how organizational climate affects self-reported productivity in a savings and credit cooperative in Portoviejo, Ecuador. Cooperatives, operating under non-profit models aimed at economic inclusion, face the challenge of maintaining productivity while ensuring employee well-being. The aim was to measure the relationship between perceptions of organizational climate and self-reported productivity, providing empirical data to inform management strategies. The research adopted a quantitative approach, utilizing a questionnaire based on validated tools and applied to 39 workers, ensuring a representative sample with a 90% confidence level. For data analysis, linear regression was employed after normalizing productivity data using the Box-Cox transformation. The results revealed an overall organizational climate score of 82.05%, with satisfaction as the highest-rated dimension (82.05%) and motivation as the lowest (78.72%). Self-reported productivity scored 77.83%, reflecting a relatively high level but with room for improvement. Regression analysis identified motivation as the main determinant of productivity, showing a significant positive effect, while deficiencies in communication had a considerable negative impact. These findings have methodological implications, demonstrating the utility of combining validated tools for local contexts, and practical implications, highlighting the need to enhance motivation and optimize internal communication as key strategies to improve productivity and workplace well-being.